Effect of water-cooling shock on fracture initiation and morphology of high-temperature granite: Application of hydraulic fracturing to enhanced geothermal systems. (1st May 2023) - Xue, Yi; Liu, Shuai; Chai, Junrui; Liu, Jia; Ranjith, P.G.; Cai, Chengzheng; Gao, Feng; Bai, Xue
Abstract: Deep geothermal energy exploitation is primarily accomplished using an enhanced geothermal system (EGS) to extract heat from hot dry rock (HDR). The use of hydraulic fracturing technology to build large-scale fracture networks is essential for improving the EGS heat extraction efficiency. Water-cooling shock on high-temperature rock degrades the mechanical properties of the rock while increasing the fracturing effect of HDR. A thermal–hydraulic–mechanical coupling model is proposed herein to investigate the effect of water-cooling shock on fracture initiation and morphology in HDR hydraulic fracturing. The validity of the coupling model is confirmed using theoretical analytical solutions and physical experimental results, such as hydraulic fracturing experiments on high-temperature granite, as well as analytical solutions for the stress shadow effect and fracture initiation pressure. The numerical simulation is performed using a coupling model to investigate the characteristics of fracture propagation and damage evolution during the HDR hydraulic fracturing process as well as to investigate the fracturing effect of water-cooling shock on high-temperature rock. Finally, the effects of initial rock temperature, in-situ stress, and heat transfer coefficient on fracture morphology are investigated. The results show that the combined effects of tensile strength deterioration water-cooling shock, thermal stress caused by cold shrinkage, and pore water pressure are primarily responsible for the initiation and propagation of hydraulic fractures. The water-cooling shock can considerably reduce the fracture initiation pressure, induce more secondary fractures, and form more complex fracture networks. The initial temperature and heat transfer coefficient of the rock affect the thermal stress and tensile strength deterioration. The formation of an intricate fracture network can be aided by a high initial rock temperature, a large surface heat transfer coefficient, and small in-situ stress differences. Highlights: A THM coupling model is established to analyze the cracking mechanism of HDR hydraulic fracturing. Water-cooling shock can cause deterioration of rock mechanical parameters. The effect of water-cooling shock on fracture initiation and morphology in HDR hydraulic fracturing is identified Water-cooling fracturing tests on high-temperature granites are conducted to validate the numerical simulations.